Optimización mediante diseño de mezclas de sinéresis y textura sensorial de Yogur natural batido de Leche de Cabra (Capra aegagrus hircus) utilizando tres tipos de Hidrocoloides - Martinez Martell, Lino Martin (2017)
The effect of the combination of three proportions of hydrocolloids (gelatin, pectin and cornstarch) on the syneresis and sensory texture of the natural yogurt beaten with goat milk was investigated using a Simplex Mixture with Amplified Centroide. The optimal combinations were obtained to obtain a low syneresis value (50.25%) and a higher sensory texture score of 3.30 (4 was the rating = "I like moderately"), obtaining optimum gelatine, pectin and cornstarch values of 0.83 %, 0.83% and 0.83%, respectively. The most adequate model to represent the behavior of the sensory texture was the quadratic model with R2 values of 0.888 and adjusted R2 of 0.748. There was also a significance level of p> 0.05 for syneresis, a result that indicates the relativity of the treatments. Finally, to validate the results of the research, the values obtained by the optimization were compared with real values, for which a sample of natural yogurt with the optimum proportions of hydrocolloids was elaborated, and an analysis of syneresis and sensorial texture was carried out again, which Provided values of 40.3% in syneresis formation and 3.8 ("I like moderately"), respectively